Analisa Kreativitas Up Selling Sebagai Bagian Tugas Dan Tanggung Jawab Server Di Sofia Restaurant The Gunawarman Luxury Residence Jakarta Selatan - Asep Parantika; Dicky Cecep Irawan (Jurnal Sains Terapan Pariwisata, 2021)
Hotel is a service accommodation that has facilitie’s in it, is intended for the public and commercially managed. The Hotel has several classification based on plans and goals in the construction of a hotel. Restaurant is a place that provides food, drinks and support services in a restaurant. Food and Beverage is an organization in charge of making food into a dish that is ready to be enjoyed as well as a container in the provision of food, beverages and food and beverage delivery services. Up Selling or personal selling is a strategy used to increase income, especially in Sofia Restaurant, The Gunawarman Luxury Residence. This writing is written with the aim to find out how the up selling strategy that is done by waiter/s in Sofia Restaurant in increasing revenue and to find out the constraints faced and efforts to resolve waiters’ obstacles in conducting up selling activities at Sofia Restaurant. The research method used is a qualitative research method that is described descriptively. The server is the name for a waiter or waitress who is developing at this time, which is usually the name used by restaurants that implement the semi-fine dining service. and the main task of the server is to serve guests who come to the restaurant, before starting to work the server must use a uniform and body makeup to make it look neat and elegant. A server also needs information about the quality and taste of dishes that are owned at the restaurant where the server works, An understanding of the product that the server wants to offer is very important, so that guests get the correct explanation and corresponding The results of this research in this Final Project show that Up Selling is included in the duties and responsibilities of a server at Sofia Restaurant The Gunawarman Luxury Residence.